MENGUNGKAP KEMUKJIZATAN ILMIAH DALAM AL-QUR’AN - Masyhuri Putra (UIN SUSKA RIAU, 2015)
There are many cues and scientific facts from the verses of the Qur’an. Almost since 15 centuries ago, the Qur’an has been much more first offensive and uncover various studies and scientific facts. Since from the creation of the universe, the heavens and the earth, humans, animals, plants, to the science and renewable technologies developed in the 19th and the 20th century. It is often heard the phrase stating that the Qur’an be a reference source scientists in various fields of study. Thus, this expression is not only a justification of the faith of a Muslim to his holy book. But it is also a challenge to prove the correctness and authenticity of the content inside. It also proves that the Qur’an is not engineered by Muhammad as alleged a little amount of local and abroad scientists. Studies and researches have shown, that what the Qur'an in line with the theory of the newest sciences though. No one else in the world litigation, but Islam speaks and gives the views and solutions in its solving.